External quality assurance of HER2 fluorescence in situ hybridisation testing: results of a UK NEQAS pilot scheme. Issue 7 (8th September 2006) - Bartlett, John M S; Ibrahim, Merdol; Miller, Keith; Jasani, Bharat; Morgan, John M; Ellis, Ian; Kay, Elaine; Magee, Hilary; Barnett, Sarah
Abstract : Background and Aims: Trastuzumab provides clinical benefit for advanced and early breast cancer patients whose tumours over-express or have gene amplification of the HER2 oncogene. The UK National External Quality Assessment Scheme (NEQAS) for immunohistochemical testing was established to assess and improve the quality of HER2 immunohistochemical testing. However, until recently, no provision was available for HER2 fluorescence in situ hybridisation (FISH) testing. A pilot scheme was set up to review the performance of FISH testing in clinical diagnostic laboratories. Methods: FISH was performed in 6 reference and 31 participating laboratories using a cell line panel with known HER2 status. Results: Using results from reference laboratories as a criterion for acceptable performance, 60% of all results returned by participants were appropriate and 78% either appropriate or acceptable. However, 22.4% of results returned were deemed inappropriate, including 13 cases (4.2%) where a misdiagnosis would have been made had these been clinical specimens. Conclusions: The results of three consecutive runs show that both reference laboratories and a proportion of routine clinical diagnostic (about 25%) centres can consistently achieve acceptable quality control of HER2 testing. Data from a significant proportion of participating laboratories show that further steps are required, including those taken via review of performance under schemes such as NEQAS, to improve quality of HER2 testing by FISH in the "real world".